Pengembangan Program Tahfidz Al-Qur’an Berbasis Pengabdian kepada Masyarakat di Desa Gunung Sari, Kabupaten Tangerang: Development of a Community-Based Qur’an Memorization Program through Community Service in Gunung Sari Village, Tangerang Regency - Bryand Brasco Amroe; Ima Iklima; Mohamad Mualim (Khadimul Mujtama’: Journal of Community Service, 2025)
This community service program was implemented in Gunung Sari Village, Mauk District, Tangerang Regency, with a focus on developing a community-based Qur’an memorization (tahfidz) program. The program was motivated by limited Qur’anic reading accuracy among children, inadequate learning facilities, and the absence of an effective and educational evaluation model for memorization. The objective of this community service was to improve the quality of Qur’an memorization learning through tahsin and tahfidz mentoring, strengthening learning facilities through the waqf of Qur’an manuscripts, and organizing Musabaqah Hifdzil Qur’an as a means of evaluation and motivation. The implementation employed a participatory approach by involving Qur’an teachers, mosque administrators, parents, and children as the main subjects of the activities. The results indicate an improvement in the quality of Qur’anic recitation and memorization, increased learning motivation among participants, and stronger community awareness and involvement in supporting the tahfidz program. The waqf of Qur’an manuscripts contributed to a more conducive and consistent learning environment, while Musabaqah Hifdzil Qur’an functioned as an educational evaluation and strengthened social participation. This program demonstrates that the development of village-level tahfidz programs requires a collaborative and sustainable approach.